An expert consensus document on the management of cardiovascular manifestations of Fabry disease - Linhart, Aleš; Germain, Dominique P; Olivotto, Iacopo; Akhtar, Mohammed M; Anastasakis, Aris; Hughes, Derralynn; Namdar, Mehdi; Pieroni, Maurizio; Hagège, Albert; Cecchi, Franco; Gimeno, Juan R; Limongelli, Giuseppe; et al. (European journal of heart failure, 2020)
Fabry disease (FD) is an X-linked lysosomal storage disorder caused by pathogenic variants in the α-galactosidase A (GLA) gene that leads to reduced or undetectable α-galactosidase A enzyme activity and progressive accumulation of globotriaosylceramide and its deacylated form globotriaosylsphingosine in cells throughout the body. FD can be multisystemic with neurological, renal, cutaneous and cardiac involvement or be limited to the heart. Cardiac involvement is characterized by progressive cardiac hypertrophy, fibrosis, arrhythmias, heart failure and sudden cardiac death. The cardiac management of FD requires specific measures including enzyme replacement therapy or small pharmacological chaperones in patients carrying amenable pathogenic GLA gene variants and more general management of cardiac symptoms and complications. In this paper, we summarize current knowledge of FD-related heart disease and expert consensus recommendations for its management.
Keywords: GLA gene; Fabry disease; Fabryho nemoc; konsensus; Cardiomyopathy; Consensus; Enzyme Replacement Therapy; alfa-galaktosidasa; Humans; alpha-Galactosidase; Heart Failure; lidé; srdeční selhání; Fabry Disease; Enzyme replacement therapy; enzymová substituční terapie